THE IMPACT OF OBESITY ON THE DEVELOPMENT OF HYPERTENSION IN CHILDREN – A LITERATURE REVIEW - Klaudia Ostrowicz,; Kacper Bartosik,; Dawid Furtek,; Izabela Lekan,; Iwona Pudełko,; Zuzanna Zięba,; Michał Lenart,; Kinga Kurenda, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Childhood obesity is a growing global health concern that significantly increases the risk of developing hypertension during childhood, leading to serious health consequences. This review aims to present the current state of knowledge regarding the relationship between obesity and hypertension in children, with particular emphasis on pathophysiological mechanisms and prevention strategies.Current Knowledge: Among all risk factors, overweight and obesity have the greatest impact, correlating proportionally with the degree of blood pressure elevation, especially systolic pressure. Studies have shown that the association between BMI and blood pressure is strongest during puberty. This relationship is influenced by complex mechanisms, including excessive activation of the sympathetic nervous system, the renin–angiotensin–aldosterone system (RAAS), hormonal imbalances, and chronic inflammation induced by adipokines. Additionally, excess adipose tissue mechanically compresses the kidneys, causing sodium retention and blood pressure elevation, while hyperinsulinemia enhances sodium reabsorption and vascular resistance, further contributing to hypertension development. These factors act synergistically, resulting in persistent dysregulation of blood pressure from an early age. Treatment primarily involves lifestyle modification, with pharmacotherapy (ACE inhibitors, ARBs, GLP-1 receptor agonists) reserved for cases resistant to non-pharmacological interventions.Summary: The available literature unequivocally indicates that obesity constitutes a significant health threat from an early age and increases the risk of serious adult diseases. Given the involvement of numerous modifiable pathophysiological mechanisms and the rising prevalence of these conditions, early prevention, health education, and an interdisciplinary treatment approach are of paramount importance.